Applying The Egra Technique in Teaching Simple Present Tense and Simple Past Tense - M, Rita; Riyanti , Dwi; Yuliana , Yohanes Gatot Sutapa (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aimed to determine whether there is a difference in the mastery of simple present and past tense, especially in the writing aspect, between the tenth-grade students learning using the EGRA technique and the Lecturing technique at MA Ushuluddin Singkawang. This study employed a quantitative method with a quasi-experimental design. The study population is 150 students, and the sampling technique is cluster random sampling. We selected the participants from two classes of tenth-grade students from MA Ushuluddin Singkawang academic year 2023/2024, dividing them into the control and experimental groups. This study employs a test that consists of a pretest and a posttest. In this research, the data analysis technique was MANOVA (Multivariate Analysis of Variances). In the findings, the researcher indicated that each test showed a significant result. Finally, the researcher employed MANOVA to address the hypothesis testing. The researcher discovered a significance level of 0.00, less than 0.05, in the results, leading to the acceptance of Ha1, Ha2, and Ha3, and the rejection of H01, H02, and H03. The conclusion is that there is a difference in the mastery of simple present tense and simple past tense, whether one by one or simultaneously, especially in the writing aspect, between the tenth-grade students who are learning using the EGRA Technique and the Lecturing technique at Ma Ushuluddin Singkawang.